Mathematical Modeling and Numerical Simulation of Central Retinal Artery Occlusion (CRAO) with Asymmetric Stenosis (Statistics, Optimization & Information Computing, 2025)
This study focuses on the analysis of arterial blood flow through a stenotic region with asymmetric stenosis in the case of Central Retinal Artery Occlusion (CRAO). Three different stenotic shapes are examined in this research: Bell-Cosine shape, Cosine-Elliptical shape, and Bell-Elliptical shape. The present study marks the first initiative to perform numerical analysis on three stenotic shapes. The finite volume method was employed to construct the blood flow model, which was solved using the SIMPLE algorithm. To support the implementation of this model, several simulation comparisons were made with existing models, and computational results for various parameter values were presented as contours and graphs. Numerical simulations were conducted to investigate the influence of the stenosis shape, position, and thickness on the velocity and pressure in the retinal blood vessels. High flow profiles with minor disturbances are observed near the origin of the stenotic artery for all geometric shapes. The pressure profile also shows elevated values near the sharp edges of the stenotic region. Among the three models, the Cosine-Elliptical shape yields the highest flow velocity, while the Bell-Cosine shape produces the highest pressure and wall shear stress. The validation of MATLAB results using ANSYS confirmed the accuracy of the model, ensuring that the MATLAB simulation is reliable for further studies.